MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Araújo Filho, Luiz Paulo da Silva; Athié, Ivan (LexCult: revista eletrônica de direito e humanidades, 2019)
Mensagem dos Dirigentes do TRF2 - biênio 2019/2021.